DGAT1 protects tumor from lipotoxicity, emerging as a promising metabolic target for cancer therapy. (1st November 2020) - Cheng, Xiang; Geng, Feng; Guo, Deliang
ABSTRACT: We recently demonstrated that glioblastoma, the most lethal brain cancer, upregulates diacylglycerol O-acyltransferase 1 (DGAT1) to store excess fatty acids into triglycerides to prevent lipotoxicity and promote tumor growth. Targeting DGAT1 resulted in marked tumor cell death by triggering extensive oxidative stress, indicating that DGAT1 could be a promising target for cancer therapy.